Comparative Analysis of Mesenchymal Stem Cell Cultivation in Fetal Calf Serum, Human Serum, and Platelet Lysate in 2D and 3D Systems - Kirsch, Marline; Rach, Jessica; Handke, Wiebke; Seltsam, Axel; Pepelanova, Iliyana; Strauß, Sarah; Vogt, Peter; Scheper, Thomas; Lavrentieva, Antonina (Frontiers in Bioengineering and Biotechnology, 2021)
In vitro two-dimensional (2D) and three-dimensional (3D) cultivation of mammalian cells requires supplementation with serum. Mesenchymal stem cells (MSCs) are widely used in clinical trials for bioregenerative medicine and in most cases, in vitro expansion and differentiation of these cells are required before application. Optimized expansion and differentiation protocols play a key role in the treatment outcome. 3D cell cultivation systems are more comparable to in vivo conditions and can provide both, more physiological MSC expansion and a better understanding of intercellular and cell-matrix interactions. Xeno-free cultivation conditions minimize risks of immune response after implantation. Human platelet lysate (hPL) appears to be a valuable alternative to widely used fetal calf serum (FCS) since no ethical issues are associated with its harvest, it contains a high concentration of growth factors and cytokines and it can be produced from expired platelet concentrate. In this study, we analyzed and compared proliferation, as well as osteogenic and chondrogenic differentiation of human adipose tissue-derived MSCs (hAD-MSC) using three different supplements: FCS, human serum (HS) and hPL in 2D. Furthermore, online monitoring of osteogenic differentiation under the influence of different supplements was performed in 2D. hPL-cultivated MSCs exhibited a higher proliferation and differentiation rate compared to HS- or FCS-cultivated cells. We demonstrated a fast and successful chondrogenic differentiation in the 2D system with the addition of hPL. Additionally, FCS, HS and hPL were used to formulate Gelatin-methacryloyl (GelMA) hydrogels in order to evaluate the influence of the different supplements on the cell spreading and proliferation of cells growing in 3D culture. In addition, the hydrogel constructs were cultivated in media supplemented with three different supplements. In comparison to FCS and HS, the addition of hPL to GelMA hydrogels during the encapsulation of hAD-MSCs resulted in enhanced cell spreading and proliferation. This effect was promoted even further by cultivating the hydrogel constructs in hPL supplemented media.